Estrategia didáctica “Figuras y puntos” y su influencia en la iniciación al aprendizaje de la estadística en el área de matemática en los niños y niñas de cinco años de la I.E N°288 “Ana Sofía Guillena Arana” del distrito de Rioja - Águila Vásquez, Karen Del (2010)
The statistics as branch of the mathematics is an essential instrument of the quantitative knowledge of the population, anyone else natural resources and the human societies's manifestation; However his teaching proves to be difficult, for his complex character, in order to the professors and furthermore his learning in order to great part of the initial- level boys and girls. Hence it has happened to me that to accomplish the investigation with regard to this matter need coming into question as objective has been seen, through the present study: Experiencing You represent the didactic strategy's influence And points in the initiation to the learning of the statistics of the mathematics area in the five - years boys and girls of the l. and. N. the study's realization is important because the statistics as branch of the mathematics is useful to pick up, to process, to examine and to interpret data or information; And than in spite of being once his teaching in the Dissent Curricular National in order to boys and girls of five years was indicated, she is being neglected. That's why, you represent didactic strategy and points, far from becoming converted in a tuition strategy, and instrument is for the better the low índices learning in the mathematics area and very especially in the related to the statistics. study was structured taking as person giving a reference the existent- investigations background and another theories such 1 have a meal: Piaget's genetic theory, theory Bruner's cultural member of Vigotsky and the theory of the learning for observation. Taking as person giving a reference mentioned theories, fact-finding hypothesis was formulated: You represent the learning level of the statistics in boys and girls than music exposed to the didactic strategy and points; it will increase mainly than in those boys and girls that do not do the strategy's use. The sign once was considerad in order to the stLidy was elected intervening the aleatory sampling simple, among all the sections with boys and girls of five years of her Jnstitution Educative N. In the election at random, Patitos in arder to the experimental group and the section determined the section himself Hormiguitas in arder to the group control such. To the sign administrated him a pre test to evaluate the initiation level to the statistics's learning that they were having You represent the boys and girls befare the didactic strategy's application And points; Next ten sessions developed learning following the methodology once was proposed for the didactic strategy Figures and points. Once concluded this stage, he applied himself again the behind test, so 1 eat to the group control knob to determine the manufactured effects for the strategy to the experimental group. Once obtenidos the data of the pre and after test, he carne from to the analysis and respective interpretation the same things, getting confirmed You take part than the didactic strategy's application And the initiation level improved Points significantly to the statistics's learning promoting averages learning of achievement in start and in process ( 7.4) to in process achievement and once was foreseen ( 13.05 ), such 1 have a meal show it you try them of hypothesis.